Predictors of provider- initiated HIV testing and counseling refusal by outpatient department clients in Wolaita zone, Southern Ethiopia: a case control study - Wolde Facha; Wondewosen Kassahun; Abdulhalik Workicho (BMC, 2016)
Abstract Background Despite different strategies designed to rapidly identify HIV infected individuals, majority of HIV-infected people are unaware of their sero-status in developing countries. The objective of this study was to assess predictors of provider-initiated HIV testing and counseling (PITC) refusal by outpatient department (OPD) clients in Wolaita zone, Southern Ethiopia. Methods Facility based unmatched case control study was conducted on outpatient department clients in randomly selected seven health facilities in Wolaita zone, Southern Ethiopia in February 2012. A total of 291 participants (97 cases and 194 controls) were included in our study. Cases were patients who refused HIV test while controls were patients who tested for HIV after provider-initiated HIV testing and counseling (PITC) recommendation by outpatient department (OPD) clinicians. We used both quantitative and qualitative methods of data collection. Pretested interviewer administered questionnaires were used to collect quantitative data by trained nurses, and in-depth interview with 14 OPD clinicians was conducted by principal investigator to supplement quantitative findings. Bivariate and multivariate analyses were done to identify independent predictors of provider-initiated HIV testing and counseling refusal by OPD clients. Result Study participants who had stigmatizing attitude [AOR = 6.09, (95 % CI: 1.70, 21.76)], who had perceived risk for HIV infection [AOR = 5.23, (95 % CI: 2.22, 12.32)], who did not perceive the benefits of provider-initiated HIV testing and counseling [AOR = 4.64, (95 % CI: 1.79, 12.01)], who did not get minimum recommended pretest information from their providers [AOR = 2.98, (95 % CI: 1.06, 8.35)], who ever not heard of provider-initiated HIV testing and counseling service [AOR = 2.41, (95 % CI: 1.14, 5.09)], and who were from urban area [AOR = 2.40, (95 % CI = 1.26, 4.57)] were more likely to refuse provider-initiated HIV testing and counseling service than their counterparts. Conclusion Knowledge on HIV/AIDS, attitude towards people living with HIV/AIDS and perceived risk for HIV infection by clients were the major barriers for provider-initiated HIV testing and counseling acceptance. Health professionals working at outpatient department should give due attention to overcome these barriers so as to enhance HIV testing acceptance by their clients.